Response to second treatment after initial failed treatment in a multicenter prospective infantile spasms cohort. (12th September 2016) - Knupp, Kelly G.; Leister, Erin; Coryell, Jason; Nickels, Katherine C.; Ryan, Nicole; Juarez‐Colunga, Elizabeth; Gaillard, William D.; Mytinger, John R.; Berg, Anne T.; Millichap, John; Nordli, Douglas R.; Joshi, Sucheta; et al.
Summary: Objective: Infantile spasms (IS) represent a severe epileptic encephalopathy presenting in the first 2 years of life. Recommended first‐line therapies (hormonal therapy or vigabatrin) often fail. We evaluated response to second treatment for IS in children in whom the initial therapy failed to produce both clinical remission and electrographic resolution of hypsarhythmia and whether time to treatment was related to outcome. Methods: The National Infantile Spasms Consortium established a multicenter, prospective database enrolling infants with new diagnosis of IS. Children were considered nonresponders to first treatment if there was no clinical remission or persistence of hypsarhythmia. Treatment was evaluated as hormonal therapy (adrenocorticotropic hormone [ACTH] or oral corticosteroids), vigabatrin, or "other." Standard treatments (hormonal and vigabatrin) were compared to all other nonstandard treatments. We compared response rates using chi‐square tests and multivariable logistic regression models. Results: One hundred eighteen infants were included from 19 centers. Overall response rate to a second treatment was 37% (n = 44). Children who received standard medications with differing mechanisms for first and second treatment had higher response rates than other sequences (27/49 [55%] vs. 17/69 [25%], p < 0.001). Children receiving first treatment within 4 weeks of IS onset had a higher response rate to second treatment than those initially treated later (36/82 [44%] vs. 8/34 [24%], p = 0.040). Significance: Greater than one third of children with IS will respond to a second medication. Choosing a standard medication (ACTH, oral corticosteroids, or vigabatrin) that has a different mechanism of action appears to be more effective. Rapid initial treatment increases the likelihood of response to the second treatment.